Targeting Androgen Receptor with Boesenbergia rotunda Phytoconstituents: A Computational-based Perspective - Najla Yasmintia Widarso; Ari Anggi Mahwati; Irene Ivory Sibuea; Dzava Prawinsyah Fairus Ismail; Bintang Satrio Mahardika; Dhania Novitasari (Indonesian Journal of Cancer Chemoprevention, 2025)
Prostate cancer is characterized by abnormal cell proliferation within the prostate gland, driven in part by the activation of androgen receptor (AR) upon binding with testosterone. The receptor, therefore, represents a critical therapeutic target in prostate cancer management. Boesenbergia rotunda or fingerroot (or temu kunci in Indonesia), a medicinal plant widely used in traditional medicine, has been reported to exhibit diverse pharmacological activities, including anticancer effects. However, despite these promising bioactivities, no molecular level or computational studies have been conducted to explore its interaction with AR. In this study, the anticancer potential of eighteen secondary metabolites from B. rotunda rhizome was investigated in silico against the AR to identify new therapeutic candidates. The test ligands were evaluated for their physicochemical properties in accordance with Lipinski’s rule of five, ADME/Tox predictions, pharmacophore screening, and molecular docking, in comparison with the reference drug bicalutamide. Among the evaluated compounds, boesenbergin A demonstrated the strongest binding affinity to AR, with a binding energy of –11.89 kcal/ mol and an inhibition constant of 1.92 nM. Importantly, boesenbergin A engaged amino acid residues, including TRP: 741, like bicalutamide, indicating comparable binding interactions. These findings suggest that boesenbergin A holds substantial promise as a natural anticancer lead compound targeting the AR and warrants further investigation as a potential therapeutic agent for prostate cancer.Keywords: Boesenbergia rotunda, boesenbergin A, prostate cancer, in silico.